Potential survival gains in the treatment of myocardial infarction. Issue 22 (6th August 2009) - Chew, D P; Huynh, L T; Liew, D; Astley, C; Soman, A; Brieger, D
Abstract : Objectives: To evaluate the potential impact of complete implementation of guideline recommendations in myocardial infarction (MI) care, and contrast this with new innovations. Design: Modelling of potential events prevented from literature-based treatment effects and observed guideline recommendation utilisation rates. Setting: Hospital-based care. Participants: Nationwide registry of 1630 patients with MI adjusted for age, gender and GRACE score extrapolated to a population of 10 000 patients. Interventions: Literature-based efficacy estimates associated with guideline-recommended treatments and a putative treatment providing a 10–30% 12-month event reduction. Main outcome measures: Mortality and recurrent MI or stroke by 30 days and 30 days to 12 months. Results: Adjusted-mortality rates for optimally managed patients with ST-segment MI (STEMI) and non-ST-segment MI (NSTEMI) to 30 days were 0.6% and 2.5%, respectively. Adjusted mortality from 30 days to 12 months was 1.8% among optimally managed patients. No reperfusion occurred in 31% of patients with STEMI. Fewer than four guideline treatments were prescribed in 26% of patients at discharge. Compared with in-hospital care, better application of secondary prevention treatments provided the greater absolute gains (STEMI 23 lives/10 000 patients by 30 days, NSTEMI 43 lives/10 000 by 30 days and secondary prevention 104 lives/10 000 by 12 months). A putative novel treatment reducing mortality by 30% among optimally managed patients would save a further 4 lives/10 000 by 12 months. Conclusions: Potential gains from improved clinical effectiveness in MI care are likely to compare favourably with benefits achieved though innovations, and should inform priorities in research and implementation strategies for improving MI outcomes.